2010
DOI: 10.1016/j.jcms.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rhBMP-2 on bone formation and osseointegration in different implant systems after sinus-floor elevation. An in vivo study on sheep

Abstract: SUMMARY.Background: Several studies have reported certain bone morphogenic proteins (BMPs) to have positive effects on bone generation. Although some investigators have studied the effects of human recombinant BMP (rhBMP-2) in sinus augmentation in sheep, none of these studies looked at the placement of implants at the time of sinus augmentation. Furthermore, no literature could be found to report on the impact that different implant systems, as well as the positioning of the implants had on bone formation if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 40 publications
5
32
0
2
Order By: Relevance
“…Therefore, E-BMP-2 could potentially be an optimal solution since it has been shown to have an effectiveness similar to that of C-BMP-2 but at a relatively low production cost [Yano et al, 2009]. Nevertheless, although a large number of studies have reported positive effects of C-BMP-2 in a variety of animal models and clinical situations [Hanisch et al, 1997;Gutwald et al, 2010], the application of E-BMP-2 in the field of dentistry still requires additional evidence regarding its efficiency and safety. In the dental field, several reports have already shown positive results of E-BMP-2 application in alveolar bone formation [Huh et al, 2011[Huh et al, , 2012, but there is still a need to investigate and confirm the effectiveness of E-BMP-2 in bone augmentation and implant stability in a sinus lift model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, E-BMP-2 could potentially be an optimal solution since it has been shown to have an effectiveness similar to that of C-BMP-2 but at a relatively low production cost [Yano et al, 2009]. Nevertheless, although a large number of studies have reported positive effects of C-BMP-2 in a variety of animal models and clinical situations [Hanisch et al, 1997;Gutwald et al, 2010], the application of E-BMP-2 in the field of dentistry still requires additional evidence regarding its efficiency and safety. In the dental field, several reports have already shown positive results of E-BMP-2 application in alveolar bone formation [Huh et al, 2011[Huh et al, , 2012, but there is still a need to investigate and confirm the effectiveness of E-BMP-2 in bone augmentation and implant stability in a sinus lift model.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep show a similar weight, size, bone and joint structure and display both cortical and trabecular bone remodeling cycles comparable to humans. Sheep are subject to research in the maxillofacial area, including osteosynthesis and fracture healing and dental implants, and facilitate the ideal anatomical conditions to assess augmentation procedures such as sinus augmentations (Gutwald et al, 2010(Gutwald et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Ethisorb is successfully used as nonwoven cell scaffolds for cartilage tissue engineering (Rotter et al, 1998). It has been shown in bone surgery that bone regeneration can be induced by using the osteoconductive potential of lactide acid (Merten and Becker, 2002), with evidence of increased bone implant contact after sinus floor elevation in sheep (Gutwald et al, 2010). Clinical results showed that periosteum-derived osteoblasts on Ethisorb Ò matrix promote mineralized trabecular bone 3 months after implantation (Schimming and Schmelzeisen, 2004).…”
Section: Discussionmentioning
confidence: 99%